Exploring BCL2 regulation and upstream signaling transduction in venetoclax resistance in multiple myeloma: potential avenues for therapeutic intervention - Fonseca, Rodrigo; Zhu, Yuan Xiao; Bruins, Laura A.; Ahmann, Joseph; de Bonolo Campos, Cecilia; Braggio, Esteban; Chen, Xianfeng; Arribas, Mariano; Darvish, Susie; Welsh, Seth; Meermeier, Erin; Mangalaparthi, Kiran K.; et al. (Blood cancer journal (New York), 2025)
Investigating venetoclax (VTX) resistance in multiple myeloma (MM) is crucial for the development of novel therapeutic strategies to tackle resistance. We conducted a multi-omic characterization of established VTX-resistant isogenic human myeloma cell lines (HMCL) and primary MM patient samples pre- and post-VTX treatment. Transcriptomic and proteomic analysis revealed that resistance was largely associated with BCL-2 family protein dysregulation, including upregulation of anti-apoptotic proteins such as MCL-1, BCL-XL, BCL-2, and downregulation of pro-apoptotic members. Notably, the re-introduction of BIM into resistant cells restored VTX sensitivity and synergized with MCL-1 inhibitors. Upstream signaling pathways, including growth factor receptor tyrosine kinase (RTK) and phosphoinositide-3-kinase (PI3K) were implicated in this dysregulation. Simultaneous inhibition of MCL-1, BCL-XL, and upstream PI3K, RTK (FGF, EGF, and IGF1) mediated signaling enhanced VTX sensitivity. Post-translational modifications of MCL-1, particularly its stabilization via acetylation and phosphorylation, were investigated, although their inhibition only marginally increased VTX sensitivity. Lastly, the inhibition of AURKA and mitochondrial respiration also improved VTX sensitivity in some resistant HMCLs. Our findings suggest that combining VTX with MCL-1 and BCL-XL inhibitors or PIK3/RTK inhibitors holds potential for overcoming resistance. The study illustrates the importance of understanding molecular determinants of resistance to develop tailored therapeutic strategies.